STRATEGI PEMASARAN UNTUK MENINGKATKAN PENDAPATAN PENGUSAHA KERIPIK TEMPE DI SANAN - Indriani (Fakultas Pertanian Universitas Tompotika Luwuk, 2023)
Tempe chips are one of the snacks that can generate income for food entrepreneurs. Tempe chips entrepreneurs need a good marketing strategy in managing their business. Production and product marketing techniques among tempe chip craftsmen are more or less the same, but the prices and quality offered are different. The research subjects were tempeh chips entrepreneurs who were a source of information to obtain data. The object of research is a strategy to increase the income production of tempeh chips entrepreneurs. Location and time of research December 2022 in Sanan, Malang city. The location determination was done purposively. The approach used is qualitative. The analysis used in this research is Structural Equation Modeling (SEM) Analysis. The research results show that the three variables, namely costs, prices and income, are most effective by using the kiosk method, because the sales results are higher. Meanwhile, based on the structural equation modeling analysis, the most influential variable is the kiosks.